Kegiatan Pendampingan Usaha Pada Sanggar Kesenian Sunda Di Tangerang - Untari, Dhian Tyas; Satria, Budi; Winarso, Widi (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2020)
Art is a product of human taste and initiative. At present, traditional arts are being eroded by the stream of modernization. So, the assistance in the